2014
DOI: 10.1007/s10552-014-0389-z
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-1, growth hormone, and daily cycling estrogen are associated with mammographic density in premenopausal women

Abstract: Frydenberg et.al 01.07.2015 2 Background: Mammographic density represents epithelial and stromal proliferation, while

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Although the sample size is too small to make definitive conclusions, one possible explanation for this observation may be related to the proliferative role of the IGF-1 axis on breast epithelium [26, 48]. Our findings thus support future studies to investigate the biochemical changes in the breast tissue before and after WLS.…”
Section: Discussionsupporting
confidence: 71%
“…Although the sample size is too small to make definitive conclusions, one possible explanation for this observation may be related to the proliferative role of the IGF-1 axis on breast epithelium [26, 48]. Our findings thus support future studies to investigate the biochemical changes in the breast tissue before and after WLS.…”
Section: Discussionsupporting
confidence: 71%
“…Individuals adapted to NSW experience lower GH nocturnal release, more frequent daily pulses and sporadic random releases (46). GH and IGF-1 promote breast cell proliferation and both have been associated with higher MD among women with high levels of estrogen (47).…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism by which IGF-1 may raise risk in younger women is by increasing breast density in pre-menopausal women, a known risk factor for cancer [ 653 ]. In addition, laboratory studies have shown that IGF-1 can regulate the growth and increase the proliferation of breast cancer cells (MCF-7) grown in vitro [ 654 ] and decrease the death of mammary tumor cells in laboratory animals [ 655 ].…”
Section: Evidence Linking Environmental Factors and Breast Cancermentioning
confidence: 99%